Effects of Lupron and surgical castration on fecal androgen metabolite concentrations and intermale aggression in capybaras (Hydrochoerus hydrochaeris). Issue 2 (18th December 2020) - Yu, Jennifer H.; Brown, Janine; Boisseau, Nicole; Barthel, Tony; Murray, Suzan
Abstract: To curb agonistic interactions in a bachelor group of three male capybaras ( Hydrochoerus hydrochaeris ), a single dose of leuprolide acetate (Lupron®) was used in an attempt to chemically sterilize the males. Concurrently, fecal androgen metabolite (FAM) concentrations were quantified via enzyme immunoassay to monitor changes in testosterone production after injection of the gonadotropin‐releasing hormone agonist. When Lupron proved ineffective in suppressing intraspecific aggression, surgical castration was performed on two males, with continued noninvasive endocrine monitoring. In all three capybaras, FAM concentrations increased initially as a result of the luteinizing hormone surge, but then decreased significantly following chemical sterilization. Surgical castration resulted in further, persistent declines in FAM concentrations in two males, while the third, intact male demonstrated a rise in FAM to pre‐Lupron concentrations at 8.5 and 9.5‐month postadministration. Despite successful suppression of sperm and testosterone production, intermale aggression continued, ultimately necessitating separation of the animals and transfer to other holding institutions. Under this set of conditions, a single Lupron dose was inadequate for suppressing intraspecific aggression in a group of three males with a pre‐established history of aggression. Graphical abstract: Fecal androgen metabolite concentrations in male capybaras following chemical and surgical sterilization. Research Highlights: Chemical sterilization with leuprolide acetate resulted in downregulation of sperm and testosterone production, but did not reduce intermale aggression among three capybara males. Similarly, subsequent surgical castration of two males was unsuccessful in managing agonistic interactions.